KEBIJAKAN PERCEPATAN PENANGGULANGAN KEMISKINAN OLEH TIM KOORDINASI PENANGGULANGAN KEMISKINAN (TKPK) DI KABUPATEN KEPULAUAN MERANTI TAHUN 2011-2012 - T. Mohd. Faisal; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study aims to determine the results acceleration of poverty reduction by theCoordinating Team for Poverty Reduction (TKPK) in Meranti Islands Regencyyear 2011-2012, and understanding the limiting factor in efforts to accelerate thepoverty reduction. This study used qualitative methods. Data collectiontechniques in this study were interviews and documentation search, then describedby means of descriptive. From the findings of the data obtained, policies issuedTKPK Meranti Islands Regency in poverty reduction is determine priority areasand targets of poverty reduction interventions, Budgeting analyze povertyreduction programs, make poverty reduction strategy, monitoring of povertyreduction programs, and coordination in efforts to accelerate poverty reduction.Acceleration of poverty reduction strategies in Meranti Islands Regency as it hasbeen by TNP2K is repair of social protection programs, improve access to basicservices, empowerment of the poor, and creating inclusive development. In theimplementation of poverty reduction programs in Meranti Islands Regency, Thereare several inhibiting factors such as Communication, Resources, disposition andbureaucratic structures.Keywords: TKPK, Poverty reduction, Meranti Islands Regency